Floppy Cloth: Textile Exhibition Strategies Inside the White Cube. (2nd October 2019) - Hemmings, Jessica
Abstract: Exhibition display has a considerable impact on the public's understanding of and respect for textiles. This article revisits 13 exhibitions held between 2005 and 2018, many of which I have previously written about in exhibition reviews, that offer innovative and thoughtful installation solutions. The examples I have selected for discussion include both textile design and textile art – genres that share a common material but pose specific exhibition challenges. Rather than focus on curation, this article attends to the seemingly pedestrian decisions of exhibition installation. Examples are organized into three groups: bolts of cloth considers the display of lengths and samples predominantly of printed textiles; the bed and the wall focuses on pieced textiles displayed on these two distinct surfaces; the final group of examples gathers together works where integrated installation solutions are solved, and often even named, as aspects of the artwork. My intention in gathering together these admittedly eclectic examples is to inspire greater consideration of the impact display decisions have on the public's appreciation and respect for textiles.